Effects of weekly hippotherapy frequency on gross motor function and functional performance of children with cerebral palsy: a randomized controlled trial - Alessandra Vidal; Jorge Manuel Gomes de Azevedo Fernandes; Ivanilda Costa da Rosa Gutierres; Franciele Cascaes da Silva; Rudney Silva; Paulo José Barbosa Gutierres Filho (Desafio Singular, 2021)
Objective: To verify whether hippotherapy once or twice a week has a different effect on gross motor function and functional performance in children with cerebral palsy. Methods: This trial had 20 children (age 2 to 5 years and 11 months) with cerebral palsy who were assigned to the groups once a week (n = 9) or twice a week (n = 11) and underwent 30-minute hippotherapy sessions for 16 weeks. The instruments used were the Gross Motor Function Measure (GMFM) and the Pediatric Evaluation of Disability Inventory (PEDI), assessed at baseline and after 16 weeks. Results: A significant time effect was observed for both groups without significant interactions between groups. Conclusions: Hippotherapy improved the gross motor function and functional performance of children with cerebral palsy, regardless of the weekly frequency of the sessions. This result has relevant clinical implications, since hippotherapy has a high cost and the prescription of weekly sessions could make this treatment more available for this population. Key-words: Equine-assisted therapy, Cerebral Palsy, Heavy Motor Function, Functional Performance